Loquat fruit ripening is associated with root depletion. Nutritional and hormonal control - Reig, Carmina; Mesejo, Carlos; Martínez-Fuentes, Amparo; Martínez-Alcántara, Belén; Agustí, Manuel (2017)
In woody species, it is known that there is a competition for nutrients, water and carbohydrates between root and fruit-shoot systems, however the influence of root development on fruit quality has received little attention. This research aims to identify the network of mechanisms involved in loquat (Eriobotrya japonica Lindl.) fruit ripening in connection with root activity. The study includes root growth rate measurements paralleling the ongoing fruit developmental stages, photosynthate translocation to the root by using 13CO2 tracing, and nitrogen fractions (Nsingle bondNH4+, Nsingle bondNO3−, and N-proteinaceous) as well as their upward translocation to the fruit. The role of hormones (IAA, zeatin and ABA) in regulating the responses is also addressed. The experiment was conducted during two consecutive years on adult and 3-year-old loquat trees from early fruit developmental stage (10% of final size, 701 BBCH scale) to fully developed fruit colour (809 BBCH scale). This approach revealed that root development depends on the growing fruit sink strength, which reduces carbohydrates translocation to the roots and prevents them for further elongation. A nitrate accumulation in roots during the active fruit growth period takes place, which also contributes to slowing elongation and paralleled reduced ammonium and proteinaceous nitrogen concentrations. Concomitantly, the concentration of IAA and zeatin were lowest while that of ABA was highest when root exhibited minimum elongation. The depletion in zeatin and nitrogen supply by the roots paralleling the high ABA transport to the fruit allowed for colour break. These results suggest that loquat fruit changes colour by reducing root growth, as fruit increases sugars and ABA concentrations and reduces nitrogen and zeatin concentrations.